Investigating the impact of leadership dynamics, job performance, and organizational climate on sustainable development in Chinese enterprises - Ran Xu; Rozaini Rosli (Problems and Perspectives in Management)
Type of the article: Research Article Abstract Chinese leadership dynamics have a significant impact on job performance in Chinese enterprises, influencing long-term success and fostering innovation, which highlights the importance of a positive organizational atmosphere in enhancing employee motivation. This study aims to examine how transformation and ethical leadership dynamics influence employee empowerment, organizational learning, and the subsequent long-term sustainability and job performance in Chinese industries. Data were collected from 500 employees across various Chinese industries, e.g., manufacturing, technology, and service. Partial least squares structural equation modeling (PLS-SEM) was employed to analyze the data. The results reveal that transformational leadership (β = 0.45, p< 0.001), employee empowerment (β = 0.45, p< 0.001), and organizational learning (β = 0.28, p< 0.001) significantly enhance organizational climate, which in turn strongly influences job performance (β = 0.50, p< 0.001). Organizational climate also mediates the effects of transformational leadership (indirect effect: β = 0.23, p< 0.001), employee empowerment (indirect effect: β = 0.16, p< 0.001), and organizational learning (indirect effect: β = 0.14, p< 0.001) on job performance. Furthermore, ethical leadership moderates the impact of transformational leadership (β = 0.19, p< 0.001) and employee empowerment (β = 0.15, p< 0.01) on organizational climate. These findings emphasize the importance of integrating ethical and transformational leadership, employee empowerment, and continuous learning to foster a supportive organizational climate and drive sustainable development. This study offers actionable insights for organizational leaders and policymakers, contributing to a deeper understanding of leadership and organizational dynamics that facilitate long-term success.